toner
Patent Information
- Application Number
- JP2020205423
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-12-10
Smart Images

Figure 0007630981000005 
Figure 0007630981000006 
Figure 0007630981000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner set for use in an electrophotographic system, an electrostatic recording system, an electrostatic printing system, and a toner jet system. [Background technology]
[0002] As copiers and printers become more widespread, the performance required of toners has become more advanced. In recent years, a digital printing technology called print on demand (hereinafter also referred to as POD), which prints directly without going through a plate-making process, has been attracting attention. This POD has an advantage over conventional offset printing because it can handle small-lot printing, printing with different contents for each sheet (variable printing), and distributed printing. When considering the application of an image forming method using toner to the POD market, it is required to stably obtain print products with high image quality even when outputting a large amount at high speed over a long period of time in various environments. One of the factors that degrade the quality of print products is the phenomenon in which toner melts onto the surface of the photoconductor drum, causing uneven image density, whiteouts, and image flow. In recent years, there has been a trend toward the development of smaller toner particles of about 4 to 7 μm in order to improve resolution and sharpness and faithfully reproduce latent images, and such smaller particle sizes tend to make toner melt onto the photoconductor drum. Methods for suppressing the fusion and adhesion of toner to the surface of the photosensitive drum have been proposed in the following patent documents. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-49452 A [Patent Document 2] JP 2017-142399 A
[0004] In Patent Document 1, two types of silica particles with different BET values are mixed in a specific ratio of amounts added and a specific average particle size ratio, and a metal oxide having a certain surface area and shape factor is added to the toner, which makes the toner less likely to deteriorate even with long-term use, and by polishing the photoconductor drum, the toner is less likely to melt onto the photoconductor drum. Furthermore, Patent Document 2 proposes that abrasive particles such as strontium titanate particles be added to silica particles having a specified compression cohesion degree and particle compression ratio as an external toner additive to ensure the cleaning performance of the photosensitive drum and prevent the toner from fusing to the photosensitive drum. Summary of the Invention [Problem to be solved by the invention]
[0005] However, while the configurations disclosed in Patent Documents 1 and 2 have a certain degree of effectiveness in cleaning the surface of the photosensitive drum, depending on the conditions, the polishing effect may not be sufficient, and toner may melt and adhere to the photosensitive drum. An object of the present invention is to provide a toner that can further suppress the fusion of the toner to the photosensitive drum and suppress the occurrence of image density unevenness, blank areas, and image deletion. [Means for solving the problem]
[0006] According to the present invention, A toner comprising toner particles containing a binder resin, and silica particles and strontium titanate particles present on the surfaces of the toner particles, The number average particle size of the primary particles of the silica particles is 80 to 200 [nm], The silica particles have a bulk density of 0.30 to 0.60 [g / mL] when compressed at 60 kPa; the adhesion rate of the silica particles on the toner particle surface is 50 to 97%, The strontium titanate particles have a number average particle size of 10 to 60 nm. The adhesion rate of the strontium titanate particles on the surface of the toner particles is 50 to 97%. the law of nature, The silica particles contain iron atoms in an amount of 20 ppm or more and 2000 ppm or less. A toner is provided. Further, according to the present invention, A toner comprising toner particles containing a binder resin, and silica particles and strontium titanate particles present on the surfaces of the toner particles, The number average particle size of the primary particles of the silica particles is 80 to 200 [nm], The silica particles have a bulk density of 0.30 to 0.60 [g / mL] when compressed at 60 kPa; the adhesion rate of the silica particles on the toner particle surface is 50 to 97%, The strontium titanate particles have a number average particle size of 10 to 60 nm. the adhesion rate of the strontium titanate particles on the surface of the toner particles is 50 to 97%, The toner is provided in which the silica particles contain aluminum atoms in an amount of 200 ppm or more and 2000 ppm or less. Further, according to the present invention, A toner comprising toner particles containing a binder resin, and silica particles and strontium titanate particles present on the surfaces of the toner particles, The number average particle size of the primary particles of the silica particles is 80 to 200 [nm], The silica particles have a bulk density of 0.30 to 0.60 [g / mL] when compressed at 60 kPa; the adhesion rate of the silica particles on the toner particle surface is 50 to 97%, The strontium titanate particles have a number average particle size of 10 to 60 nm. the adhesion rate of the strontium titanate particles on the surface of the toner particles is 50 to 97%, The silica particles provide a toner having a compression degree of 0.01 to 0.25. Effect of the Invention
[0007] According to the present invention, a blocking layer is formed in which silica particles and strontium titanate particles are uniformly mixed, thereby providing a toner that suppresses the fusion of the toner to the drum surface and suppresses the occurrence of image density unevenness, white spots, and image flow. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram of an image forming apparatus. [Diagram 2] FIG. 2 is a schematic diagram of a cleaner portion on the surface of the photoconductor drum. [Diagram 3] FIG. 2 is a schematic enlarged view of a cleaner blocking layer according to the present invention. [Figure 4] FIG. 2 is a schematic enlarged view of a conventional cleaner blocking layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described in detail. A toner comprising toner particles containing a binder resin, and silica particles and strontium titanate particles present on the surfaces of the toner particles, The number average particle size of the primary particles of the silica particles is 80 to 200 [nm], The silica particles have a bulk density of 0.30 to 0.60 [g / mL] when compressed at 60 kPa; the adhesion rate of the silica particles on the toner particle surface is 50 to 97%, The strontium titanate particles have a number average particle size of 10 to 60 nm. The adhesion rate of the strontium titanate particles on the surface of the toner particles is 50 to 97%.
[0010] The adhesion rate of the silica particles on the surface of the toner particles is After printing 1,000 sheets, the yield is 91-97%. It is preferable that the efficiency is 50 to 79% after printing 100,000 sheets, and The adhesion rate of the strontium titanate particles on the surface of the toner particles is After printing 1,000 sheets, the yield is 87-94%. It is preferable that the efficiency is 59 to 79% after printing 100,000 sheets. The lower limit and upper limit of a preferred range of the adhesion rate of the silica particles after printing 1,000 sheets and after printing 100,000 sheets, and The lower and upper limits of the preferred range of the adhesion rate of the strontium titanate particles after printing 1,000 sheets and after printing 100,000 sheets are: This was determined based on the results of the examples described below.
[0011] The strontium titanate particles are preferably rectangular or cubic. The silica particles preferably contain iron atoms in an amount of 20 ppm or more and 2000 ppm or less. The silica particles preferably contain aluminum atoms in an amount of 200 ppm or more and 2000 ppm or less. The silica particles preferably have a compression degree of 0.01 to 0.25.
[0012] By using such a toner of the present invention, the above-mentioned problem of toner melting onto the photosensitive drum can be suppressed. The present inventors presume the mechanism of this effect achieved by using the toner of the present invention as follows.
[0013] The reason why toner melts onto the photosensitive drum is that the abrasive performance of the cleaning blade on the drum surface is reduced. A blocking layer 22 composed mainly of inorganic particles is formed between the cleaning blade 21 and the surface of the photoreceptor drum 20 (see FIG. 2). The state of formation of this blocking layer 22 affects the polishing effect of the cleaning blade 21 on the surface of the photoreceptor drum 20. In forming this blocking layer, spherical silica particles are used as an external toner additive, and a certain amount of these particles detach from the toner and aggregate to form the blocking layer, thereby exerting a polishing effect on the photoreceptor drum surface.
[0014] Furthermore, to improve the polishing effect, rectangular or cubic strontium titanate particles are used as an external toner additive. A certain amount of these particles detach from the toner and form a blocking layer together with the silica particles, thereby improving the polishing effect on the photosensitive drum surface. However, depending on the printing conditions and environment, toner melting onto the photoconductor drum can cause output image abnormalities such as uneven image density, blank areas, and image deletion. This is because the blocking layer, which is made up of silica particles and strontium titanate particles, has fewer areas where the strontium titanate particles, which have a high abrasive effect, come into contact with the photoconductor drum surface (see Figure 4).This is because the silica particles have aggregated and are not mixed uniformly with the strontium titanate particles.
[0015] Therefore, by using the above-mentioned specific silica particles, the silica particles are less likely to aggregate than conventional silica particles, and are more uniformly mixed with the strontium titanate particles. As a result, as shown in Figure 3, the probability that the strontium titanate particles 24 come into contact with the surface of the photoconductor drum 20 is increased, thereby improving the polishing effect. It is presumed that the reason why the silica particles are not easily agglomerated is that they contain a certain amount of iron atoms, so that even if frictional charging occurs, the charge is easily dissipated, making electrostatic agglomeration difficult to occur.
[0016] In the present invention, preferred embodiments for achieving the object will be described in detail below.
[0017] [Silica particles] The toner of the present invention has silicon oxide (silica) particles on the surface of the toner particles, and the number average particle size of the primary particles is 80 nm to 200 nm. By using silica particles having a particle size in the above range, the toner surface can maintain convex portions even when subjected to mechanical load in a developing device, the toner charge amount is less likely to decrease, and this contributes to reducing variations in reflection density and fogging in non-image areas.
[0018] The silica particles used in the toner of the present invention have a bulk density of 0.30 to 0.60 [g / mL] when pressed at 60 kPa. If the bulk density is less than 0.30 g / mL, the cleaner blocking layer is not formed firmly and becomes brittle, resulting in insufficient polishing effect on the photoconductor drum. If the bulk density exceeds 0.60 g / mL, the abrasive tends to condense and is difficult to mix uniformly with the strontium titanate particles, which may result in less of the strontium titanate particles, which have a high abrasive effect, coming into contact with the surface of the photosensitive drum.
[0019] The silica particles used in the present invention are particles mainly composed of silica (i.e., SiO2), and can be produced by known production methods such as a combustion method, a melting method, hydrothermal synthesis, etc. Among them, in order to further enhance the effect of suppressing the charge relaxation in a high-temperature and high-humidity environment, and from the viewpoint of having high resistance and being less susceptible to the influence of humidity, silica particles produced by the combustion method or the melting method are more preferable.
[0020] The combustion method is a method in which a siloxane compound is vaporized, the siloxane gas is introduced into a burner together with a carrier gas such as nitrogen, and the siloxane gas is diffused and mixed with a combustion-supporting gas such as oxygen, and then burned to produce large-diameter silica particles.Another combustion method is a method in which silicon tetrachloride is burned at high temperature together with a mixed gas of oxygen, hydrogen, and a dilution gas such as nitrogen, to produce silica particles (fumed silica). The melting method is a method in which a slurry of metal silicon particles is sprayed into a flame to cause an oxidation reaction and to form the particles into spheroids, thereby obtaining silica particles.
[0021] In the present invention, from the viewpoint of achieving desired values of the number average particle size of the primary particles of the silica particles and the content of iron atoms, a preferred example is a combustion method in which siloxane gas is combusted to produce silica particles. Examples of siloxane compounds that can be vaporized to obtain siloxane gas include hexamethylcyclotrisiloxane and octamethylcyclotetrasiloxane. In the present invention, the silica particles used in the present invention can be obtained by incorporating iron atoms, and preferably further incorporating aluminum atoms, into the silica particles. As a method for incorporating these metal atoms into silica particles, a method of using a siloxane compound containing these metal atoms can be adopted.
[0022] The silica particles may be surface-treated with a fatty acid or a metal salt thereof, a disilylamine compound, a halogenated silane compound, silicone oil, a silane coupling agent, a titanium coupling agent, or the like. These hydrophobic treatments are preferred in that they can improve the charge stability of the toner, particularly in high-temperature and high-humidity environments. Among these, n-octylethoxysilane treatment, 3,3,3-trifluoropropyltrimethoxysilane treatment, and hexamethyldisilazane treatment are preferred in that they enhance the effect of charge stability.
[0023] The mixing with the toner particles can be performed using a known mixer such as a Henschel mixer, Mechano Hybrid (manufactured by Nippon Coke Corporation), a Super Mixer, or Nobilta (manufactured by Hosokawa Micron Corporation), and the device is not particularly limited. The amount of the silica particles added in the present invention is 0.5% by mass or more and 15% by mass or less based on the toner.
[0024] [Strontium titanate particles] The strontium titanate particles used in the toner of the present invention have a number-average particle size of primary particles of 10 to 60 nm. If the number-average particle size of the strontium titanate particles is less than 10 nm, the effect of polishing the surface of the photoreceptor drum cannot be sufficiently obtained. If the number-average particle diameter of the strontium titanate particles exceeds 60 nm, when a blocking layer is formed by mixing the strontium titanate particles with silica particles, the number of particles that come into contact with the surface of the photoreceptor drum tends to vary widely.
[0025] The strontium titanate particles used in the present invention preferably have a rectangular parallelepiped or cubic shape. The surfaces of the strontium titanate particles may be treated with fatty acids or metal salts thereof, disilylamine compounds, halogenated silane compounds, silicone oils, silane coupling agents, titanium coupling agents, stearic acid-based substances, etc. This treatment is advantageous in terms of adhesion to the toner particle surface and charging.
[0026] The content (coverage) of strontium titanate particles on the toner particle surface is preferably 0.25 to 5.00 times the content (coverage) of silica particles on the toner particle surface in order to assist the charging of the silica particles having a large particle size. If the content (coverage) of strontium titanate particles is less than 0.25 times the content (coverage) of silica particles, the amount of strontium titanate used in the blocking layer may be insufficient, and sufficient cleaning effect may not be obtained on the photosensitive drum surface. If the content (coverage) of strontium titanate particles is more than 5.00 times the content (coverage) of silica particles, the blocking layer formed when mixed with the silica particles may contain too much strontium titanate, making the blocking layer brittle, or an ideal blocking layer may not be formed, reducing the cleaning effect on the photosensitive drum surface.
[0027] The production of strontium titanate particles used in the present invention will be described. One of the production methods is a normal pressure heating reaction method. In this case, a mineral acid peptized product of a hydrolyzate of a titanium compound is used as the titanium oxide source, and a water-soluble acidic strontium compound is used as the strontium oxide source. The mixture of these is reacted while adding an alkaline aqueous solution at 60°C or higher, and then the particles are treated with an acid to produce the particles.
[0028] (Normal pressure heating reaction method) As the titanium oxide source, a mineral acid peptized product of a hydrolyzate of a titanium compound is used. Preferably, metatitanic acid having an SO3 content of 1.0 mass% or less, preferably 0.5 mass% or less, obtained by a sulfuric acid method, is peptized by adjusting the pH to 0.8 to 1.5 with hydrochloric acid. Metatitanic acid having an SO3 content of more than 1.0 mass% is not preferred because peptization does not proceed.
[0029] As the strontium oxide source, metal nitrates, hydrochlorides, etc., for example, strontium nitrate and strontium chloride can be used. As the aqueous alkaline solution, a caustic alkali can be used, and among them, an aqueous sodium hydroxide solution is preferable.
[0030] In the above-mentioned production method, factors that affect the particle size of the obtained strontium titanate particles include the following. The mixing ratio of the titanium oxide source and the strontium oxide source during the reaction, the concentration of the titanium oxide source at the beginning of the reaction, the temperature and the addition rate when the alkaline aqueous solution is added, etc. In order to obtain the desired particle size and particle size distribution, the above factors can be appropriately adjusted. In order to prevent the formation of carbonate during the reaction process, it is preferable to prevent contamination with carbon dioxide gas by, for example, carrying out the reaction under a nitrogen gas atmosphere.
[0031] In the above-mentioned manufacturing method, factors that affect the dielectric constant of the obtained strontium titanate particles include conditions / operations that disrupt the crystallinity of the particles. In particular, in order to obtain particles with a low dielectric constant even in the case of strontium titanate of the present invention, it is preferable to carry out an operation that applies energy that disrupts the crystal growth while increasing the concentration of the reaction solution. A specific example of such a method is to add microbubbles with nitrogen to the crystal growth process.
[0032] The mixing ratio of the titanium oxide source and the strontium oxide source during the reaction is preferably 0.9 to 1.4 in terms of the molar ratio of SrO / TiO2, and more preferably 1.05 to 1.20. When the SrO / TiO2 molar ratio is 1.0 or less, the reaction product is likely to contain not only metal titanate but also unreacted titanium oxide. Since the strontium oxide source has a relatively high solubility in water while the titanium oxide source has a relatively low solubility in water, when the SrO / TiO2 molar ratio is 1 or less, the reaction product is likely to contain not only metal titanate but also unreacted titanium oxide. The concentration of the titanium oxide source at the beginning of the reaction is preferably 0.05 mol / L to 1.3 mol / L in terms of TiO2, and more preferably 0.08 mol / L to 1.0 mol / L.
[0033] The temperature at which the aqueous alkaline solution is added is 100°C or higher, requiring a pressure vessel such as an autoclave, and is practically preferably in the range of 60°C or higher and lower than 100°C. The slower the rate of addition of the aqueous alkaline solution, the larger the particle size of the metal titanate particles obtained, and the faster the rate of addition, the smaller the particle size of the metal titanate particles obtained. The rate of addition of the aqueous alkaline solution is preferably 0.001 equivalent / h or higher and 1.2 equivalent / h or lower, and more preferably 0.002 equivalent / h or higher and 1.1 equivalent / h or lower, relative to the charged raw material, and can be appropriately adjusted depending on the particle size to be obtained.
[0034] (Acid treatment) It is preferable to further treat the strontium titanate particles obtained by the above-mentioned normal pressure heating reaction with an acid. When performing normal pressure heating reaction to synthesize strontium titanate particles, if the mixing ratio of the titanium oxide source and the strontium oxide source exceeds 1.0 in molar ratio of SrO / TiO2, the metal source other than titanium that remains unreacted after the reaction is completed reacts with carbon dioxide gas in the air. Then, impurities such as metal carbonates are generated. In addition, if impurities such as metal carbonates remain on the surface, the organic surface treatment agent cannot be uniformly coated due to the influence of the impurities when performing organic surface treatment to impart hydrophobicity. Therefore, it is preferable to perform acid treatment to remove unreacted metal sources after adding an alkaline aqueous solution.
[0035] [Other external additives] In addition to the silica particles having the above-mentioned particle size, the toner of the present invention may contain other inorganic fine powders as necessary to adjust the charge amount and fluidity. The inorganic fine powders may be added internally to the toner particles or may be mixed with the toner particles as an external additive. As the external additive, inorganic fine powders such as silica, titanium oxide, aluminum oxide, magnesium oxide, and calcium carbonate are preferred. The inorganic fine powders may be hydrophobized with a hydrophobizing agent such as a stearic acid compound, a silane compound, silicone oil, or a mixture thereof.
[0036] The external additive is preferably used in an amount of 0.1 parts by mass to 10.0 parts by mass based on 100 parts by mass of toner particles. The toner particles and the external additive can be mixed using a known mixer such as a Henschel mixer.
[0037] [Binding resin] The binder resin used in the toner of the present invention is not particularly limited, and the following polymers or resins can be used.
[0038] For example, the following can be mentioned: Homopolymers of styrene and its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-acrylic acid ester copolymers, styrene-methacrylic acid ester copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, and styrene-acrylonitrile-indene copolymers; polyvinyl chloride, phenolic resins, naturally modified phenolic resins, naturally modified maleic acid resins, acrylic resins, methacrylic resins, polyvinyl acetate, silicone resins, polyester resins, polyurethanes, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins, and petroleum-based resins.
[0039] Of these, it is preferable to use polyester resins from the viewpoints of low-temperature fixability and charge control.
[0040] The polyester resin preferably used in the present invention is a resin having a "polyester unit" in the binder resin chain. Specific examples of components constituting the polyester unit include divalent or higher alcohol monomer components and acid monomer components such as divalent or higher carboxylic acids, divalent or higher carboxylic acid anhydrides, and divalent or higher carboxylic acid esters.
[0041] Examples of the divalent or higher alcohol monomer component include the following: alkylene oxide adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and 1,4-butanediol. , neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, 1,3,5-trihydroxymethylbenzene, etc.
[0042] Among these, the alcohol monomer component that is preferably used is an aromatic diol, and the alcohol monomer component that constitutes the polyester resin preferably contains the aromatic diol in a proportion of 80 mol % or more.
[0043] On the other hand, examples of the acid monomer components such as divalent or higher carboxylic acids, divalent or higher carboxylic acid anhydrides, and divalent or higher carboxylic acid esters include the following: aromatic dicarboxylic acids or anhydrides thereof, such as phthalic acid, isophthalic acid, and terephthalic acid; alkyl dicarboxylic acids or anhydrides thereof, such as succinic acid, adipic acid, sebacic acid, and azelaic acid; succinic acid or anhydrides thereof substituted with an alkyl or alkenyl group having 6 to 18 carbon atoms; and unsaturated dicarboxylic acids or anhydrides thereof, such as fumaric acid, maleic acid, and citraconic acid.
[0044] Among these, preferred acid monomer components are polyvalent carboxylic acids such as terephthalic acid, succinic acid, adipic acid, fumaric acid, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and anhydrides thereof.
[0045] The acid value of the polyester resin is preferably 20 mgKOH / g or less from the viewpoints of pigment dispersibility and triboelectric charge stability.
[0046] The acid value can be adjusted to the above range by adjusting the type and amount of monomers used in the resin. Specifically, the acid value can be controlled by adjusting the alcohol monomer component ratio / acid monomer component ratio and molecular weight during resin production. In addition, the acid value can be controlled by reacting the terminal alcohol with a polyacid monomer (e.g., trimellitic acid) after ester condensation polymerization.
[0047] <Examples of binder resin production> (Production example of polyester resin) Polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane: 80.0 mol% based on the total number of moles of polyhydric alcohol Polyoxyethylene (2.2)-2,2-bis(4-hydroxyphenyl)propane: 20.0 mol% based on total number of moles of polyhydric alcohol Terephthalic acid: 80.0 mol% based on the total number of moles of polycarboxylic acids Trimellitic anhydride: 20.0 mol% based on the total number of moles of polycarboxylic acids The above materials were put into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. Then, 1.5 parts by mass of tin 2-ethylhexanoate (esterification catalyst) was added as a catalyst to 100 parts by mass of the total amount of monomers. Next, the atmosphere in the flask was replaced with nitrogen gas, and the temperature was gradually raised while stirring, and the reaction was carried out for 2.5 hours while stirring at a temperature of 200°C.
[0048] The pressure in the reaction vessel was then lowered to 8.3 kPa and maintained for 1 hour, after which the vessel was cooled to 180°C and reacted as is. After confirming that the softening point measured according to ASTM D36-86 reached 110°C, the temperature was lowered to stop the reaction. The softening point (Tm) of the resulting polyester resin 1 was 115°C.
[0049] [Coloring agent] Colorants that can be contained in the toner of the present invention include the following.
[0050] As the black colorant, carbon black is mainly used, and dyes and pigments may be added as necessary. In addition, a yellow colorant, a magenta colorant, and a cyan colorant may be used to tone the color black. As the colorant, a pigment may be used alone, but it is more preferable to use a dye and a pigment in combination to improve the clarity of the color image from the viewpoint of image quality of a full-color image.
[0051] Magenta colored pigments include: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.
[0052] Magenta coloring dyes include: CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1, and other solvent dyes; CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28, and other basic dyes.
[0053] Cyan coloring pigments include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton.
[0054] Cyan coloring dyes include CI Solvent Blue 70.
[0055] Yellow coloring pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20.
[0056] Yellow coloring dyes include CI Solvent Yellow 162.
[0057] The colorant is preferably used in an amount of 0.1 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0058] [Release agent: wax] Examples of the release agent used in the toner of the present invention include the following waxes.
[0059] Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or their block copolymers; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax.
[0060] Further examples include the following: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene biphenyl amide, ethylene bisstearic acid amide, ethylene bisstearic acid amide, ethylene bisstearic acid amide, hexamethylene biphenyl ... Saturated fatty acid bisamides such as stearic acid amide; unsaturated fatty acid amides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N' dioleyl adipic acid amide, and N,N' dioleyl sebacic acid amide; aromatic bisamides such as m-xylene bisstearic acid amide and N,N' distearyl isophthalic acid amide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols, such as behenic acid monoglyceride; and methyl ester compounds having hydroxyl groups obtained by hydrogenating vegetable oils and fats.
[0061] Among these waxes, from the viewpoint of improving low-temperature fixing property and hot offset resistance, preferred are hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax.
[0062] The content of the wax is preferably 1.0 part by mass or more and 15 parts by mass or less relative to 100 parts by mass of the binder resin. When the content of the wax is in this range, it is easy to efficiently exhibit offset resistance at high temperatures.
[0063] From the viewpoint of achieving both storage stability and high-temperature offset resistance of the toner, it is preferable that the peak temperature of the maximum endothermic peak present in the temperature range of 30°C to 200°C in the endothermic curve during temperature rise measured by a differential scanning calorimeter (DSC) is 50°C to 110°C.
[0064] [Wax dispersant] In order to improve the dispersibility of the wax in the binder resin, a resin having both a polarity site similar to that of the wax component and a polarity site similar to that of the resin may be added as a wax dispersant. Specifically, a styrene-acrylic resin graft-modified with a hydrocarbon compound is preferable.
[0065] The wax dispersant improves the charge retention of the toner by introducing a cyclic hydrocarbon group or an aromatic ring into the resin portion thereof, which is preferable because it suppresses the toner particles from reducing the charge assisting properties of the strontium titanate particles of the present invention. <Production example of wax dispersant> Put the following materials into an autoclave reaction vessel equipped with a thermometer and stirrer and dissolve them thoroughly. Xylene 300.0 parts by mass Polypropylene (melting point 75°C) 10.0 parts by mass After replacing the air with nitrogen, a mixed solution of the following materials is added dropwise at 180°C over a period of 3 hours to polymerize. Styrene 73.0 parts by mass Cyclohexyl methacrylate 5.0 parts by mass Butyl acrylate 12.0 parts by mass Xylene 250.0 parts by mass The mixture was then maintained at this temperature for a further 30 minutes to remove the solvent, yielding a wax dispersant.
[0066] [Charge control agent] The toner may contain a charge control agent as necessary. Any known charge control agent may be used as the charge control agent contained in the toner, but a metal compound of an aromatic carboxylic acid is particularly preferred, as it is colorless, the toner can be charged quickly, and a constant charge amount can be stably maintained.
[0067] Examples of negative charge control agents include the following: metal salicylate compounds, metal naphthoate compounds, and metal dicarboxylate compounds. Polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate salts or sulfonate esters on the side chain, and polymeric compounds having carboxylate salts or carboxylate esters on the side chain. Boron compounds, urea compounds, silicon compounds, and calixarenes. Positive charge control agents include quaternary ammonium salts, polymeric compounds having the quaternary ammonium salts in the side chains, guanidine compounds, and imidazole compounds. The charge control agent may be added internally or externally to the toner particles. The amount of the charge control agent added is preferably 0.2 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0068] [Developer] The toner of the present invention can be used as a one-component developer, but in order to further improve dot reproducibility, it is preferable to mix it with a magnetic carrier and use it as a two-component developer. The two-component developer is also preferable in that stable images can be obtained over a long period of time.
[0069] <Magnetic carrier> The magnetic carrier may be any of the following known magnetic carriers: surface-oxidized or unoxidized iron powder, metal particles of iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium, rare earths, etc., alloy particles, and oxide particles thereof, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state, etc. More specifically, it is possible to use magnetic carriers such as ordinary ferrite, magnetite, etc., and resin-coated carriers. It is also possible to use binder-type magnetic carrier cores in which magnetic powder is dispersed in a resin.
[0070] Resin-coated carriers consist of magnetic carrier core particles and a resin coating layer that coats the surface of the magnetic carrier core particles. Examples of resins used in the resin coating layer include the following: styrene-acrylic resins such as styrene-acrylic acid ester copolymers and styrene-methacrylic acid ester copolymers; acrylic resins such as acrylic acid ester copolymers and methacrylic acid ester copolymers; fluorine-containing resins such as polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymers, monochlorotrifluoroethylene polymers, and polyvinylidene fluoride; silicone resins; polyester resins; polyamide resins; polyvinyl butyral; and aminoacrylate resins. Other examples include ionomer resins and polyphenylene sulfide resins. These resins can be used alone or in combination. The magnetic carrier of the present invention may have silica particles attached to the surface of the magnetic carrier body. By adding silica particles to the magnetic carrier body and mixing them using a mixing device such as a V-type mixer, a Henschel mixer, or a Turbula mixer, a magnetic carrier having silica particles attached to the surface of the magnetic carrier body can be obtained.
[0071] When the toner of the present invention is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio in this case is 2% by mass or more and 15% by mass or less, preferably 4% by mass or more and 13% by mass or less, in terms of the toner concentration in the two-component developer.
[0072] [Toner manufacturing method] The method for producing the toner of the present invention is not particularly limited as long as it is a conventionally known toner production method such as an emulsion aggregation method, a melt kneading method, or a dissolution suspension method. From the viewpoint of improving the dispersibility of the raw materials, the melt kneading method is preferred.
[0073] The melt-kneading method is characterized in that a toner composition, which is a raw material for toner particles, is melt-kneaded and the resulting kneaded product is pulverized. An example of the production method will be described below.
[0074] In the raw material mixing process, the materials constituting the toner particles, such as polyester resin, release agent, colorant, and other components such as charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.).
[0075] Next, the mixed materials are melt-kneaded to disperse other raw materials in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of being capable of continuous production. For example, a KTK type twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM type twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process.
[0076] The cooled resin composition is then pulverized to a desired particle size in a pulverization process. In the pulverization process, the resin composition is coarsely pulverized using a pulverizer such as a crusher, hammer mill, or feather mill, and then further pulverized using a fine pulverizer. Examples of fine pulverizers include the Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), Super Rotor (manufactured by Nisshin Engineering, Inc.), Turbo Mill (manufactured by Freund Turbo Corp.), and fine pulverizers using an air jet system.
[0077] Thereafter, if necessary, the mixture is classified using a classifier or sieve to obtain toner particles. These include the inertial classification system Elbow Jet (manufactured by Nippon Steel Mining Co., Ltd.), the centrifugal classification system Turboplex (manufactured by Hosokawa Micron Corporation), the TSP Separator (manufactured by Hosokawa Micron Corporation), and the Faculty (manufactured by Hosokawa Micron Corporation).
[0078] The number-average particle diameter of the toner particles is preferably 4.0 μm or more and 7.0 μm or less, since the effect of the external additive of the present invention can be fully obtained. Furthermore, the circularity of the toner particles may be increased by applying a mechanical impact force to the particles and performing a heat treatment using hot air or the like. In order to increase the opportunity for charge transfer between toner particles and the frictional sliding force between the toner particles and to increase the charge rise speed, the average circularity is preferably 0.962 or more and 0.972 or less.
[0079] The toner particles produced by the above-mentioned production method are mixed with selected external additives as required (external addition). Examples of mixing devices include a double cone mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.).
[0080] [Image forming method] The toner set having the color toner and the black toner of the present invention can be applied to a known image forming method. Specifically, the toner set can be suitably used in an image forming method including the following steps. A step of charging an electrostatic image carrier; A step of forming an electrostatic image on a charged electrostatic image bearing member; developing the electrostatic image with toner to form a toner image; transferring the formed toner image to a transfer material; and The process of fixing the transferred toner image onto the transfer material to form a fixed image.
[0081] The toner image forming step may include a step of forming a black toner image using a black toner of the toner set, and a step of forming a color toner image using a color toner of the toner set. If the color toners are three types, that is, a magenta toner, a cyan toner, and a yellow toner, the number of steps for the color toners is three. In the embodiment described later, the cyan toner is used as a representative color toner, and an example of a toner set of a black toner and a cyan toner is shown.
[0082] [Method for measuring bulk density of silica particles] The bulk density of the silica particles was measured using a powder flow analyzer, the powder rheometer FT-4 (manufactured by Freeman Technology). The FT-4 device was operated according to the instructions attached to it, and 10 g of a silica particle sample was placed in a dedicated container and conditioned. After that, a pressure of 60 kPa was applied using a compression tool dedicated to the FT-4, and the bulk density of the sample was measured.
[0083] <Washing method> Silica particles are extracted from the toner by a water washing method. Specifically, a sucrose aqueous solution obtained by dissolving 31.1 g of sucrose (Kishida Chemical Co., Ltd.) in 10.3 g of ion-exchanged water is added to 6 mL of Contaminon N described below in a 30 mL glass vial described below and mixed thoroughly to prepare a dispersion liquid. Contaminon N: A neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder; manufactured by Wako Pure Chemical Industries, Ltd. Glass vial: Nichiden Rika Glass Co., Ltd., VCV-30, outer diameter: 35 mm, height: 70 mm 1.0 g of toner is added to this glass vial, and the toner is left to stand until it naturally settles to prepare a pre-treatment dispersion. This dispersion is shaken for 5 minutes at a shaking speed of 200 rpm in a shaker (YS-8D type: manufactured by Yayoi Co., Ltd.) to separate the silica particles from the surface of the toner particles. A centrifuge is used to separate the toner particles from the silica particles that have been detached from the surface of the toner particles. The centrifugation process is carried out at 3700 rpm for 30 minutes. The silica particles and toner that have been detached from the surface of the toner particles and separated are collected by suction filtration, and then dried to obtain silica particles and toner after washing with water.
[0084] <Method for measuring the content of metal elements in silica particles> The silica particles obtained by repeatedly carrying out the above water washing treatment are subjected to fluorescent X-ray measurement, and the contents of iron atoms and aluminum atoms are calculated. The X-ray fluorescence measurement of each element conforms to JIS K 0119-1969, and specifically, is as follows: As a measuring device, for example, a wavelength dispersive X-ray fluorescence analyzer "Axios" (manufactured by PANalytical) is used. 2 g of sample is weighed into a cup for powder measurement recommended by PANalytical with a dedicated PP (polypropylene) film attached to the bottom, a layer of uniform thickness is formed on the bottom, and the lid is placed. Next, elements from Na to U in the silica particles are measured using the FP method under atmospheric pressure He atmosphere. At this time, it is assumed that all detected elements are oxides, and their total mass is set to 100%, and the content (mass%) of Fe2O3 and Al2O3 relative to the total mass is calculated as oxide equivalent values using the software SpectraEvaluation (version 5.0L).
[0085] <Method of measuring number-average particle diameter of toner, method of measuring adhesion rate of silica particles, and method of measuring adhesion rate of strontium titanate particles> The number-based number average particle diameter D of the toner of the present invention, the adhesion rate Z1 of the silica particles, and the adhesion rate Z2 of the strontium titanate particles can be determined by image observation using a scanning electron microscope and subsequent image processing. The number-based number average particle diameter D and adhesion rate Z of the toner of the present invention were calculated by substituting the results of observations made using a scanning electron microscope (SEM), S-4800 (manufactured by Hitachi, Ltd.) into a given formula. The area ratios of the portions originating from silica particles and strontium titanate particles were calculated by image processing based mainly on the differences in brightness and shape at an acceleration voltage of 2.0 kV. Specifically, the toner was fixed in a single layer on a sample stage for electron microscope observation with carbon tape, platinum was evaporated, and the toner was observed with a scanning electron microscope S-4800 (manufactured by Hitachi, Ltd.) under the following conditions. Observation was performed after a flushing operation. SignalName=SE(U,LA80) AcceleratingVoltage=2000Volt EmissionCurrent=10000nA WorkingDistance=6000um LensMode=High Condenser1=5 ScanSpeed=Slow4(40 seconds) Magnification=50000 DataSize=1280×960 ColorMode=Grayscale
[0086] The brightness of the secondary electron image was adjusted to 'contrast 5, brightness -5' on the control software of the scanning electron microscope S-4800. Then, the capture speed / accumulation number was set to 'Slow 4 for 40 seconds', and a projection image of the toner was obtained as an 8-bit 256-level grayscale image with an image size of 1280 x 960 pixels. From the scale on the image, the length of 1 pixel is 0.02 μm, and the area of 1 pixel is 0.0004 μm. 2 It becomes.
[0087] Next, using the obtained projection image by the secondary electrons, the projected area circle equivalent diameter and the area ratio (area%) of the part derived from the silica particles and the strontium titanate particles were calculated for 100 toner particles. The method of selecting 100 toner particles to be analyzed will be described in detail later. The area% of the part derived from the silica particles and the strontium titanate particles was calculated using the image processing software Image-Pro Plus5.1J (manufactured by Media Cybernetics).
[0088] Next, the toner particle clusters were extracted and the size of each extracted toner particle was counted. Specifically, first, to extract the toner particle clusters to be analyzed, the toner particle clusters were separated from the background. Select "Measurement" - "Count / Size" in Image-Pro Plus5.1J. In "Count / Size" "Brightness Range Selection", the brightness range was set to 50 to 255, and the low brightness carbon tape part that was reflected as the background was excluded, and the toner particle clusters were extracted. When the toner particle clusters are fixed by a method other than carbon tape, the background may not necessarily be a low brightness area, or there is a possibility that the brightness may be the same as that of the toner particle clusters in some parts. However, the boundary between the toner particle clusters and the background can be easily distinguished from the secondary electron observation image. When performing the extraction, select 4-connected in the extraction options of "Count / Size", enter smoothness 5, check "Fill Holes", and exclude toner particles located on all boundaries (outer periphery) of the image and toner particles that overlap with other toner particles from the calculation. Next, area and Feret diameter (average) were selected from the measurement items of "Count / Size," and the area selection range was set to a minimum of 100 pixels and a maximum of 10,000 pixels, and each toner particle was extracted for image analysis. One toner particle was selected from the extracted toner particle group, and the size of the part originating from that particle (number of pixels: ja) was obtained. The projected area equivalent circle diameter d1 was obtained from the obtained ja using the following formula. "Projected area equivalent circle diameter" represents the diameter of a perfect circle having the same area as the projected area of a toner particle. d1={(4×ja×0.3088) / 3.14} (1 / 2)
[0089] Next, in Image-Pro Plus5.1J's "Count / Size" "Brightness Range Selection", the brightness range was set to 140 to 255, and high brightness areas on each toner particle were extracted. By setting the area selection range to a minimum of 3 pixels and a maximum of 200 pixels, it was possible to extract high brightness areas originating from silica particles and strontium titanate particles. Particles that are not rectangular or cubic in shape are judged to be silica particles, and particles that are rectangular or cubic in shape are judged to be strontium titanate particles.
[0090] Then, for the toner particles selected when calculating ja, the size (number of pixels: ma1) of the part on the toner surface derived from the silica particles was calculated. In each toner particle, the extracted parts derived from the silica particles are scattered with a certain size, and ma1 is their total area. The coverage rate s1 of the silica particles was calculated from the obtained ma1 using the following formula. s1=(ma1 / ja)×100
[0091] Next, the following adhesion rates Z1b and Z1c of the silica particles were calculated using the following coverage rates s1a, s1b, and s1c of the silica particles and the following formula. Printing conditions: Continuous printing of 25% duty images using the actual machine at a room temperature of 30°C and a relative humidity of 80% Actual machine: A modified Canon Inc. full-color copier imageRUNNER ADVANCE C5560 II was used as the image forming device. Coverage rate s1a before printing starts Coverage rate s1b after printing 1,000 sheets Coverage rate s1c after printing 100,000 sheets Adhesion rate after printing 1,000 sheets Z1b = (s1b / s1a) x 100 Adhesion rate after printing 100,000 sheets Z1c = (s1c / s1a) x 100
[0092] The size (number of pixels: ma2) of the portion of the toner surface originating from the strontium titanate particles was determined in the same manner as for the silica particles. The coverage s2 of the strontium titanate particles was calculated from the obtained ma2 using the following formula. s2=(ma2 / ja)×100 Next, the following adhesion rates Z2b and Z2c of the strontium titanate particles were calculated using the following coverage rates s2a, s2b, and s2c of the strontium titanate particles and the following formula. Coverage rate s2a before printing starts Coverage rate s2b after printing 1,000 sheets Coverage rate s2c after printing 100,000 sheets Adhesion rate after printing 1,000 sheets Z2b = (s2b / s2a) x 100 Adhesion rate after printing 100,000 sheets Z2c = (s2c / s2a) x 100
[0093] The same process was performed on each particle of the extracted particle group until the number of selected toner particles became 50 or more. The arithmetic mean value of the obtained projected area circle equivalent diameters was defined as the number average particle diameter D of the toner of the present invention. For the adhesion rates Z1b and Z1c of silica particles and the adhesion rates Z2b and Z2c of strontium titanate particles, the same process was performed until the number of selected toner particles became 50 or more, and the arithmetic average values obtained were taken as the adhesion rates Z1b, Z1c, Z2b, and Z2c.
[0094] Measurement of the Compressibility of Silica Particles The degree of compression of the silica particles was measured using a powder flow analyzer, powder rheometer FT-4 (manufactured by Freeman Technology). The FT-4 device was operated according to the instructions attached to it, 10 g of a silica particle sample was placed in a dedicated container, and a conditioning operation was performed. Then, pressures of 15 kPa, 30 kPa, and 60 kPa were applied using a compression tool dedicated to the FT-4, and the density of the sample at each pressure was measured. The density at 60 kPa was designated as P60. Furthermore, the values of each pressure and the density were graphed, and the density P0 at a pressure of 0 (the intercept of the approximation line) was calculated from the approximation line. The degree of compression was calculated using the following formula (1). Compressibility = (P60-P0) / P60 Equation (1) EXAMPLES
[0095] The present invention will be described below with reference to Production Examples and Examples. However, the present invention is not limited to these Examples. In addition, all parts are by weight unless otherwise specified.
[0096] <Production Example of Silica Particle 1> Silica particles 1 were produced by a diffusion combustion method as follows. In producing the silica particles 1, a hydrocarbon-oxygen mixed burner with a double-tube structure in which an inner flame and an outer flame are formed was used as the combustion furnace. This burner is configured so that a two-fluid nozzle for injecting slurry is grounded at the center of the burner, and the raw material silicon compound is introduced. In addition, a flammable hydrocarbon-oxygen gas is injected from the periphery of the two-fluid nozzle, forming an inner flame and an outer flame, which are a reducing atmosphere. The atmosphere, temperature, and flame length can be adjusted by controlling the amount and flow rate of the flammable gas and oxygen. In addition, in the flame, silica particles are generated from the raw silicon compound, and the silica particles can be fused until they reach a desired particle size. After that, they are cooled and the generated silica particles are collected by a bag filter or the like to obtain silica particles of the desired particle size. As the silicon compound raw material, a hexamethylcyclotrisiloxane compound containing 200 ppm of iron atoms and 400 ppm of aluminum atoms was used to produce pre-surface-treated silica particles 1. Next, 100 parts by mass of the obtained pre-surface-treated silica particles 1 were subjected to a surface treatment with 3.9% by mass of hexamethyldisilazane to obtain silica particles 1. The number average particle size of the primary particles of the obtained silica particles 1 is shown in Table 1. Table 1 also shows the bulk density, iron atom content, aluminum atom content, and compression degree of the silica particles 1 when pressed at 60 kPa.
[0097] <Production Examples of Silica Particles 2 to 31> In the production example of silica particles 1, the number average particle size of the primary particles and the iron atom content and aluminum atom content of the hexamethylcyclotrisiloxane compound were changed to obtain silica particles 2 to 15. The number average particle size of the primary particles, the bulk density when pressurized at 60 kPa, the iron atom content, the aluminum atom content, and the compression degree of each silica particle are shown in Table 1.
[0098] [Table 1]
[0099] <Production Example of Strontium Titanate Particles 1> Metatitanic acid obtained by the sulfuric acid method was deironized and bleached, then sodium hydroxide solution was added to adjust the pH to 9.0, desulfurized, neutralized to pH 5.8 with hydrochloric acid, filtered and washed with water. Water was added to the washed cake to make a 1.5 mol / L slurry in terms of TiO2, and hydrochloric acid was added to adjust the pH to 1.5, followed by peptization.
[0100] The desulfurized and peptized metatitanic acid was collected as TiO2 and put into a 3L reaction vessel. A strontium chloride aqueous solution was added to the peptized metatitanic acid slurry so that the SrO / TiO2 molar ratio was 1.15, and then the TiO2 concentration was adjusted to 0.8mol / L. Next, the mixture was heated to 90°C while stirring and mixing, and 444mL of 10N (mol / L) sodium hydroxide aqueous solution was added over 45 minutes while nitrogen gas was micro-bubbled at 600mL / min, and then the mixture was stirred at 95°C for 1 hour while nitrogen gas was micro-bubbled at 400mL / min.
[0101] The reaction slurry was then stirred while flowing 10°C cooling water through the jacket of the reaction vessel to rapidly cool it to 15°C, and hydrochloric acid was added until the pH reached 2.0, and stirring was continued for 1 hour. The precipitate obtained was washed by decantation, and then 6N (mol / L) hydrochloric acid was added to adjust the pH to 2.0, and 7.0 mass% n-octylethoxysilane was added based on the solid content, and stirring was continued for 18 hours. The mixture was neutralized with a 4N (mol / L) aqueous sodium hydroxide solution, stirred for 2 hours, filtered and separated, and dried in the air at 120°C for 8 hours to obtain strontium titanate particles 1. Strontium titanate particles 1 showed a diffraction peak of strontium titanate when measured by powder X-ray diffraction.
[0102] When the strontium titanate particles 1 were observed under an electron microscope, the content of particles having a clearly cornered rectangular parallelepiped shape was 45% by number, and the number-average particle size was 40 nm.
[0103] <Production Examples of Strontium Titanate Particles 2-31> In the production example of strontium titanate particles 1, the mixing ratio of the titanium oxide source and the strontium oxide source during the reaction, the concentration of the titanium oxide source at the beginning of the reaction, and the temperature and addition rate when adding the alkaline aqueous solution were appropriately adjusted. As a result, strontium titanate particles 2 to 31 having the desired particle size and particle size distribution were obtained. Table 2 shows the number average particle size of the primary particles of each strontium titanate particle.
[0104] [Table 2]
[0105] <Production Example of Toner Particle 1> Binding resin 100 parts (Polyester with Tg: 57°C, acid value: 12mgKOH / g, hydroxyl value: 15mgKOH / g) CI Pigment Blue 15:3 5.7 parts 0.1 parts of 3,5-di-t-butylsalicylic acid aluminum compound Normal paraffin wax (melting point: 90°C) 5 parts The above materials were premixed in a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.), and then melt-kneaded at 160° C. using a twin-screw kneading extruder (PCM-30, manufactured by Ikegai Co., Ltd.). The obtained kneaded product was cooled, coarsely pulverized to 1 mm or less using a hammer mill, and then finely pulverized using a mechanical pulverizer (T-250, manufactured by Turbo Kogyo Co., Ltd.). The resulting finely pulverized material was classified using a Faculty (F-300, manufactured by Hosokawa Micron Corp.) The operating conditions were a classifying rotor rotation speed of 11,000 rpm and a dispersing rotor rotation speed of 7,200 rpm. In this way, negatively triboelectrically charged toner particles 1 having a weight average particle size (D4) of 5.5 μm were obtained.
[0106] 100 parts of toner particles Silica particles 1 10 parts 1-3 parts strontium titanate particles Next, the above raw materials were mixed in a Henschel mixer (FM-10C, manufactured by Nippon Coke Co., Ltd.) at a rotation speed of 67 s -1 (4000 rpm) for 2 minutes, and then sieved through a mesh with 150 μm openings to obtain toner 1. The physical properties of the obtained toner 1 are shown in Table 3.
[0107] <Production Examples of Toners 2 to 31> Toners 2 to 31 were obtained in the same manner as Toner 1, except that the silica particles 1 were changed to silica particles 2 to 31, and the strontium titanate particles 1 were changed to strontium titanate particles 2 to 31, respectively. The physical properties of the obtained Toners 2 to 31 are shown in Table 3.
[0108] [Table 3]
[0109] <Manufacturing example of magnetic core particles> (Step 1: Weighing and mixing step) ·Fe2O362.8 parts by mass ·MnCO329.4 parts by mass ·Mg(OH)26.8 parts by mass ·SrCO31.0 parts by mass The ferrite raw materials were weighed so as to obtain the above composition ratio, and then crushed and mixed for 5 hours in a dry vibration mill using stainless steel beads with a diameter of 1 / 8 inch.
[0110] Step 2 (Pre-firing): The obtained pulverized material was made into pellets of about 1 mm square using a roller compactor. The pellets were passed through a vibrating sieve with 3 mm openings to remove coarse powder, and then passed through a vibrating sieve with 0.5 mm openings to remove fine powder. The pellets were then fired in a burner-type firing furnace at 1,000°C for 4 hours in a nitrogen atmosphere (oxygen concentration 0.01% by volume) to produce calcined ferrite. The composition of the resulting calcined ferrite was as follows: (MnO) a (MgO) b (SrO) c (Fe2O3) d In the above formula, a = 0.257, b = 0.117, c = 0.007, d = 0.393
[0111] (Step 3: Crushing step) After crushing to about 0.3 mm using a crusher, 30 parts by mass of water was added to 100 parts by mass of the calcined ferrite using zirconia beads with a diameter of 1 / 8 inch, and the mixture was crushed in a wet ball mill for 1 hour. The slurry was crushed for 4 hours in a wet ball mill using alumina beads with a diameter of 1 / 16 inch to obtain a ferrite slurry (finely crushed calcined ferrite).
[0112] (Process 4: Granulation process) To the ferrite slurry, 1.0 parts by mass of ammonium polycarboxylate as a dispersant and 2.0 parts by mass of polyvinyl alcohol as a binder were added per 100 parts by mass of the calcined ferrite. Then, the mixture was granulated into spherical particles using a spray dryer (manufacturer: Okawara Kakoki Co., Ltd.). After adjusting the particle size of the obtained particles, the mixture was heated in a rotary kiln at a temperature of 650°C for 2 hours to remove the organic components of the dispersant and binder.
[0113] (Step 5: Firing step) In order to control the firing atmosphere, the material was heated from room temperature to 1,300°C in a nitrogen atmosphere (oxygen concentration 1.00% by volume) in an electric furnace over a period of 2 hours, and then fired at 1,150°C for 4 hours. The material was then cooled to 60°C over a period of 4 hours, returned from the nitrogen atmosphere to the air, and removed at a temperature of 40°C or less.
[0114] (Step 6: Sorting step) After the aggregated particles were crushed, low magnetic particles were removed by magnetic separation, and coarse particles were removed by sieving through a sieve with 250 μm openings to obtain magnetic core particles 1 having a volume distribution-based median diameter of 37.0 μm.
[0115] <Preparation of Coating Resin> Cyclohexyl methacrylate monomer 26.8% by mass Methyl methacrylate monomer 0.2% by mass Methyl methacrylate macromonomer 8.4% by mass (A macromonomer with a weight-average molecular weight of 5,000 and a methacryloyl group at one end) Toluene 31.3% by mass Methyl ethyl ketone 31.3% by mass Azobisisobutyronitrile 2.0% by mass Among the above materials, cyclohexyl methacrylate, methyl methacrylate, methyl methacrylate macromonomer, toluene, and methyl ethyl ketone were placed in a four-necked separable flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube, and a stirrer. Nitrogen gas was then introduced to replace the inside of the system with nitrogen gas. The mixture was then heated to a temperature of 80°C, azobisisobutyronitrile was added, and the mixture was refluxed for 5 hours to polymerize. Hexane was poured into the resulting reaction product to precipitate a copolymer, and the precipitate was filtered and then vacuum dried to obtain coating resin 1. The resulting coating resin 1 was dissolved in 30 parts by mass, 40 parts by mass of toluene, and 30 parts by mass of methyl ethyl ketone to obtain polymer solution 1 (solid content 30% by mass).
[0116] <Preparation of coating resin solution> ·Polymer solution 1 (resin solid content concentration 30%) 33.3% by mass Toluene 66.4% by mass Carbon black 0.3% by mass (Primary particle size 25 nm, nitrogen adsorption specific surface area 94 m 2 / g, DBP oil absorption 75mL / 100g) The above materials were dispersed for 1 hour using zirconia beads having a diameter of 0.5 mm in a paint shaker. The resulting dispersion was filtered through a 5.0 μm membrane filter to obtain a coating resin solution 1.
[0117] [Magnetic carrier manufacturing] (Resin coating process) Coating resin solution 1 was added to a vacuum degassing kneader maintained at room temperature so that the resin component was 2.5 parts by mass per 100 parts by mass of magnetic core particles 1. After addition, the mixture was stirred at a rotation speed of 30 rpm for 15 minutes, and after a certain amount of the solvent (80% by mass) had evaporated, the mixture was heated to 80°C while mixing under reduced pressure, and toluene was distilled off over 2 hours, after which it was cooled. The magnetic carrier obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 70 μm, and then classified with a wind classifier to obtain a magnetic carrier having a median diameter of 38.1 μm based on the volume distribution.
[0118] [Examples 1 to 17, Comparative Examples 1 to 14] Toner 1 and the magnetic carrier were mixed in a V-type mixer (V-10 type: Tokuju Seisakusho Co., Ltd.) for 0.5 s so that the toner concentration was 10% by mass. -1 The mixture was mixed for 5 minutes at a rotation time of 100° C. to obtain two-component developer 1. Similarly, toners 2 to 31 shown in Table 3 were mixed with a magnetic carrier to obtain two-component developers 2 to 31. In the following, Examples 10 to 17 will be referred to as Reference Examples 10 to 17, respectively.
[0119] The following print durability test was carried out using these two-component developers 1 to 17 as examples and two-component developers 18 to 31 as comparative examples, and then the toner performance was evaluated.
[0120] <Print durability test> The image forming apparatus used was a modified imageRUNNER ADVANCE C5560 II full-color copier manufactured by Canon Inc. After a durability image output test of 100,000 sheets in a high temperature and high humidity environment (temperature 30°C / relative humidity 80%, hereinafter referred to as H / H environment), evaluation was performed using the following method. During the continuous paper feed time of 100,000 sheets, the sheets were fed under the same developing and transfer conditions (without calibration) as for the first sheet. For the durability images, the image print ratio was set to 20%, and the developing bias was adjusted so that the initial image density was 1.45. The evaluation paper was plain copy paper CS-680 (A4, basis weight 68 g / m2) for the durability image output of 100,000 sheets. 2 (sold by Canon Marketing Japan Inc.) was used.
[0121] Toner Performance Evaluation <Evaluation 1> Evaluation of image whiteout and image flow After printing 100,000 sheets of images under the above conditions, a halftone image with an image density of 0.800 was printed using an X-Rite color reflection densitometer (500 series, manufactured by X-Rite). If image deletion or blank areas occur, the image dots become smaller and the image density decreases, so measurements were taken at 10 locations, and the image density difference (difference between maximum and minimum values) was confirmed and also visually. Evaluation was performed according to the following criteria, and the results are shown in Table 4. Rank A: Less than 0.025 Rank B: 0.025 or more, less than 0.050 Rank C: 0.050 or more, less than 0.075 Rank D: 0.075 or more, less than 0.100 Rank E: 0.100 or more, less than 0.300 Rank F: 0.300 or higher
[0122] <Evaluation 2> Evaluation of image density uniformity (unevenness in image density) A durability image output test of 100,000 sheets was conducted under normal temperature and humidity conditions (temperature 23°C / relative humidity 60%, hereafter referred to as N / N environment) to evaluate image density unevenness. The output image used was pattern image 1, in which 2mm-wide strips of solid areas and 18mm-wide strips of white background were repeatedly arranged in a direction parallel to the paper feed direction. At this time, the amount of toner placed on the paper in the solid areas of pattern image 1 was 0.40 mg / cm. 2 At the time when 100 sheets of the pattern image 1 were output and at the time when 100,000 sheets were output, the output was stopped once, and then a pattern image 2 in which the entire surface of the paper was a solid area was output (the amount of toner on the paper in the solid area was 0.40 mg / cm 2 ).
[0123] The image density of the entire solid image was measured at 20 random locations using an X-Rite color reflection densitometer ("500 Series", manufactured by X-Rite Corporation).The image density uniformity was evaluated at the time when 100 sheets had been printed and at the time when 100,000 sheets had been printed, using the difference between the maximum and minimum values of the image density (image density difference). The image density difference used in the evaluation is a value calculated using the following formula, and a smaller value indicates better results. Image density difference = ((Image density difference after 100 sheets have been printed) + (Image density difference after 100,000 sheets have been printed)) / 2 The evaluation criteria were set as follows. The evaluation results are shown in Table 4. Rank A: Less than 0.025 Rank B: 0.025 or more, less than 0.05 Rank C: 0.05 or more, less than 0.075 Rank D: 0.075 or more, less than 0.10 Rank E: 0.10 or more, less than 0.15 Rank F: 0.15 or higher
[0124] [Table 4]
[0125] As shown by the above results, the blocking layer, which is a uniform mixture of large silica particles and small strontium titanate particles, increases the opportunities for the small strontium titanate particles, which have a high abrasive effect, to come into contact with the drum surface, thereby suppressing the fusion of toner to the drum surface and preventing the occurrence of image density unevenness, blank areas, and image deletion. [Explanation of symbols]
[0126] 1: photoconductor drum, 2: charging device, 3: exposure device, 5: developer container, 6: developer carrier, 7: magnet, 8: regulating member, 9: intermediate transfer body, 11: transfer charger, 12: transfer material (recording medium), 13: fixing device, 15: cleaner, 16: pre-exposure, 20: photoconductor drum, 21: cleaning blade, 22: blocking layer, 23: silica particles, 24: strontium titanate particles
Claims
1. A toner comprising toner particles containing a binder resin, and silica particles and strontium titanate particles present on the surfaces of the toner particles, The number average particle size of the primary particles of the silica particles is 80 to 200 nm; The silica particles have a bulk density of 0.30 to 0.60 [g / mL] when compressed at 60 kPa; the adhesion rate of the silica particles on the surface of the toner particles is 50% to 97%; The strontium titanate particles have a number average particle size of 10 to 60 nm. the adhesion rate of the strontium titanate particles on the surface of the toner particles is 50 to 97%, The toner, wherein the silica particles contain iron atoms in an amount of 20 ppm or more and 2000 ppm or less.
2. The toner according to claim 1, wherein the silica particles contain aluminum atoms in an amount of 200 ppm or more and 2000 ppm or less.
3. A toner comprising toner particles containing a binder resin, and silica particles and strontium titanate particles present on the surfaces of the toner particles, The number average particle size of the primary particles of the silica particles is 80 to 200 nm; The silica particles have a bulk density of 0.30 to 0.60 [g / mL] when compressed at 60 kPa; the adhesion rate of the silica particles on the surface of the toner particles is 50% to 97%; The strontium titanate particles have a number average particle size of 10 to 60 nm. the adhesion rate of the strontium titanate particles on the surface of the toner particles is 50 to 97%, The toner is characterized in that the silica particles contain aluminum atoms in an amount of 200 ppm or more and 2000 ppm or less.
4. The silica particles according to any one of claims 1 to 3, wherein the degree of compression is 0.01 to 0.
25. Toner included.
5. A toner comprising toner particles containing a binder resin, and silica particles and strontium titanate particles present on the surfaces of the toner particles, The number average particle size of the primary particles of the silica particles is 80 to 200 nm; The silica particles have a bulk density of 0.30 to 0.60 [g / mL] when compressed at 60 kPa; the adhesion rate of the silica particles on the surface of the toner particles is 50% to 97%; The strontium titanate particles have a number average particle size of 10 to 60 nm. the adhesion rate of the strontium titanate particles on the surface of the toner particles is 50 to 97%, The toner is characterized in that the silica particles have a compression degree of 0.01 to 0.
25.
6. 6. The toner according to claim 1, wherein the strontium titanate particles have a rectangular parallelepiped or cubic shape.
Citation Information
Patent Citations
toner
JP2005049452A
Toner and two-component-based developer
JP2015084095A
Image formation device, process cartridge, and image formation method
JP2016110052A
Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2017142399A
Toner and image forming method
JP2020034901A